The Potential of Lignocellulosic Biomass Hydrolysates for Microbial Oil Production Using Yeasts and Microalgae - Lesetja Moraba Legodi; Kgabo L. Maureen Moganedi (International Journal of Chemical Engineering)
The use of food-based biomass and arable land for bio-oil and biofuel production could compromise global food security. Therefore, renewable and environmentally friendly oils for biofuels from oleaginous microorganisms such as yeasts and microalgae (heterotrophic and mixotrophic) are gaining interest within the scientific community. These microorganisms have shorter cultivation times and higher lipid productivity when compared to higher plants/food crops/autotrophic microorganisms. Despite many advantages, the high carbon requirements and production cost are limiting factors that hinder their deployment at a commercial scale. Lignocellulosic waste substrates are abundant and inexpensive materials that are rich in organic carbon in the form of cellulose and hemicellulose, which release bioavailable forms of sugars upon hydrolysis. Recent studies have shown the tremendous potential of the hydrolysates of these substrates to be utilized as carbon sources for biomass production and the accumulation of lipids in oleaginous hetero-/mixotrophic microorganisms. Therefore, this review highlights the potential use of lignocellulosic biomass as a low-cost carbon substrate for the cultivation of hetero-/mixotrophic microalgae and yeast for microbial oil production for commercial applications. It also examines the current status, challenges, and future prospects for the utilization of lignocellulose biomass.